ChemInform Abstract: Metal‐Free Arylations via Photochemical Activation of the Ar—OSO2R Bond in Aryl Nonaflates. Issue 8 (25th February 2014) - Raviola, Carlotta; Canevari, Veronica; Protti, Stefano; Albini, Angelo; Fagnoni, Maurizio
Abstract The reaction can be carried out using the premade ArOSO2Nf or the reagents can be made in situ.